2015
DOI: 10.1007/s10620-015-3809-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Peroxiredoxin 6 in Ischemia/Reperfusion-Induced Damage of Small Intestine

Abstract: The application of exogenous Prx6 enables normalization of the antioxidant status of the small intestine and reduction of cell destruction upon I/R-induced organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Our investigation demonstrated that MCB and mesenteric vessels have a common mechanism of reaction to I/R injury, which consists of decreased endothelium-dependent relaxation. According to our assumption, it is related to oxidative stress developed upon I/R injury of the small intestine [Bhattacharyya et al, 2014;Gordeeva et al, 2015], resulting in decreased NO bioavailability for vascular tone regulation [Garden and Granger, 2000;Vollmar and Menger, 2011].…”
Section: Discussionmentioning
confidence: 93%
“…Our investigation demonstrated that MCB and mesenteric vessels have a common mechanism of reaction to I/R injury, which consists of decreased endothelium-dependent relaxation. According to our assumption, it is related to oxidative stress developed upon I/R injury of the small intestine [Bhattacharyya et al, 2014;Gordeeva et al, 2015], resulting in decreased NO bioavailability for vascular tone regulation [Garden and Granger, 2000;Vollmar and Menger, 2011].…”
Section: Discussionmentioning
confidence: 93%
“…To test the therapeutic effect of exogenous Prx1 and Prx2 proteins, the solution of the corresponding recombinant protein was injected into the tail vein to a final concentration of 20 μg/g of bodyweight 15 min before the beginning of ischemia. Selection of the injection method and the concentrations of protein solutions was carried out according to previous studies [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…It must be noted that some Prx representatives have been investigated previously in models of artificially induced oxidative stress: total irradiation, renal ischemia-reperfusion injury, small intestine, etc. [ 13 , 14 , 15 , 16 , 17 ]. It is the Prx family proteins that have shown high efficiency in oxidative stress neutralization, which is associated with the high antioxidant activity of these enzymes and a wide range of neutralizable hydroperoxides, both organic and inorganic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there are many reasons to believe that antioxidant enzymes can be more effective in neutralising reactive oxygen species (ROS) than low-molecular-weight antioxidants. Previously, we have shown the therapeutic effects of a recombinant peroxiredoxin 6 (PRDX6) in various pathologies associated with inflammation and oxidative stress, such as intestinal hypoxia/reperfusion [ 16 ]. We believe that PRDX6 may be effective as an agent that suppresses the level of oxidative stress in diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%